“Accessibility”: A new narrative of healthcare services for people living with HIV in the capital city of Indonesia - Mahathir, Mahathir; Wiarsih, Wiwin; Permatasari, Henny (Belitung Raya Foundation, Indonesia, 2021)
Background: The progress of the fight against HIV is highlighted by significant change. HIV of the past is different from HIV of the present. Healthcare services have played an essential role in achieving the optimal goals needed to end the HIV epidemic. However, people living with HIV and those at risk of catching it (PLWH) often misunderstand the rapid growth of HIV healthcare service options.Objective: This study aimed to explore the experiences of PLWH in the healthcare services featured in this study.Methods: A qualitative phenomenological approach was used. Semi-structured interviews were conducted in 2017 with 12 PLWH who engaged with healthcare services in Jakarta, Indonesia, by using a purposive sampling technique. Semi-structured questions were asked which related to their experiences of using the services. Stevick Colaizzi Keen method was used to extract the thematic analysis of the study.Results: The study developed four essential themes of PLWH healthcare use. They were accessibility, availability at all healthcare levels, comprehensiveness of service, and affordability.Conclusion: Providing accessible healthcare services is considered essential by PLWH. It is also pivotal to helping people feel positive about the community-related healthcare services on offer. Nurse-led HIV services must maintain this progress by continuously evaluating the quality-of-service outcomes and promoting the accessibility of the services to the broader population.